2009
DOI: 10.3945/jn.109.107888
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Patterns Are Associated with Metabolic Syndrome in Adult Samoans ,

Abstract: The prevalence of metabolic syndrome has reached epidemic levels in the Samoan Islands. In this cross-sectional study conducted in 2002-2003, dietary patterns were described among American Samoan (n = 723) and Samoan (n = 785) adults (> or =18 y) to identify neo-traditional and modern eating patterns and to relate these patterns to the presence of metabolic syndrome using Adult Treatment Panel III criteria. The neo-traditional dietary pattern, similar across both polities, was characterized by high intake of l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
138
1
1

Year Published

2011
2011
2015
2015

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 99 publications
(148 citation statements)
references
References 60 publications
7
138
1
1
Order By: Relevance
“…We have no or insufficient information about the eating habits and the educational level of either the MDD patients or the primary care subjects. Eating habits have been shown to contribute to the development of the metabolic syndrome, such as overeating, increased intake of processed foods, saturated fatty acids and trans fatty acids and decreased intake of fruits and fish [9,13,16,41]. Furthermore, several studies in different countries found a negative association between the prevalence of the MetS, cardiovascular risk and the socioeconomic status, particularly in females [2,4,15,26].…”
Section: Discussionmentioning
confidence: 96%
“…We have no or insufficient information about the eating habits and the educational level of either the MDD patients or the primary care subjects. Eating habits have been shown to contribute to the development of the metabolic syndrome, such as overeating, increased intake of processed foods, saturated fatty acids and trans fatty acids and decreased intake of fruits and fish [9,13,16,41]. Furthermore, several studies in different countries found a negative association between the prevalence of the MetS, cardiovascular risk and the socioeconomic status, particularly in females [2,4,15,26].…”
Section: Discussionmentioning
confidence: 96%
“…For example, populations in Papua New Guinea suffer continuing undernutrition and infection (Ulijaszek, 2000), along with increasing BMI, prevalence of overweight (Benjamin, 2007;Ulijaszek, 1993), and central fat distribution (Norgan, 1987) largely associated with modernization since the 1950s. During this period, intake of protein, energy, and storebought foods increased (Harvey and Heywood, 1983), just as observed in Vanuatu and across the Pacific, including in Fiji (Collins et al, 1996;Taylor et al, 1992), Guam (Guerrero et al, 2008), Kiribati (King et al, 1984a;Taylor et al, 1992), Nauru (King et al, 1984b;Ringrose and Zimmet, 1979;Sicree et al, 1987;Zimmet et al, 1978), New Caledonia (Papoz et al, 1996), Samoa (Baker et al, 1986;Dibello et al, 2009;Galanis et al, 1999), the Solomon Islands (Eason et al, 1987;Friedlaender, 1987), and Tuvulu (Wicking et al, 1981).…”
Section: Global Implications Of Health Transitionmentioning
confidence: 99%
“…Numerous Pacific studies suggest that increasing rates of chronic diseases are associated with migration to urban areas (Joseph et al, 1983;Ostbye et al, 1989;Pawson and Janes, 1982;Prior et al, 1974;Salmond et al, 1985), urbanization (Baker et al, 1986;Benjamin, 2006;Coyne et al, 1984;DiBello et al, 2009;Ezeamama et al, 2006;Friedlaender, 1987;Harvey and Heywood, 1983;Hodge et al, 1995;Kende, 2001;King et al, 1994;Lindeberg et al, 1999;McGarvey et al, 1989;McGarvey, 1991;Norgan, 1995;Russell-Jones et al, 1990;Saweri, 2001;Taylor et al, 1991Taylor et al, , 1992Ulijaszek, 2003;Zimmet et al, 1978), and having relatives in urban areas, who send remittances and influence attitudes about cultural change (Ulijaszek, 2005). However, identifying specific behavioral changes associated with modernization is difficult.…”
mentioning
confidence: 99%
“…1 These high prevalences of obesity has lead to rapid rises in obesity-related diseases such as cardiovascular disease (CVD) and type 2 diabetes. 2 The rapid temporal rise of Samoan obesity and obesity-related diseases has been attributed to modernization and its associated nutritional transition, in which these developing nations are consuming more calorie-rich foods and expending less energy. 1 Although these behavioral factors are linked to obesity and obesityrelated diseases, genetic factors have also been shown to play an important role in Samoan obesity and obesity-related risk factors.…”
Section: Introductionmentioning
confidence: 99%